Better Policies from Policy-Selective Aid?. (26th June 2020) - Annen, Kurt; Knack, Stephen
Abstract: The increased policy selectivity of aid allocations observed in recent years provides aid-recipient countries with an incentive to improve policies. The paper estimates that a change in the World Bank's Country Policy and Institutional Assessment policy index from 1.5 to 2 for a recipient is associated with an increase of about 13 percent in aid. The analysis also finds a modest but statistically significant positive relationship between the global level of policy-selective aid and policy, suggesting that policy-selective aid improves policies in aid-recipient countries. This effect is properly identified, as the level of policy-selective aid in the global aid budget is exogenous to a recipient country's policy choice. Furthermore, the paper provides a game-theoretic model that establishes the link between the policy selectivity of the global budget and better recipient-country policies in equilibrium.